THE INFLUENCE OF WORKPLACE SPIRITUALITY ASPECTS ON EMPLOYEES' WORK MOTIVATION: A CASE STUDY AT MEDAN AREA UNIVERSITY - Andri Harun Siregar; Harmein Nasution; Linda T. Maas (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to analyze the influence of workplace spirituality, consisting of dimensions of meaningful work, sense of community, and alignment with organizational values, on employee work motivation. This study is motivated by the phenomenon of declining employee performance at Medan Area University in the 2016-2018 period, indicated by the results of internal audits, even though the institution has implemented quality management standards. This study uses a causal quantitative approach. The study population was all employees and permanent lecturers, with a sample of 220 respondents determined using purposive sampling techniques and the Slovin formula. Data were collected through questionnaires and analyzed using Multiple Linear Regression. The results show that the three dimensions of workplace spirituality have a positive and significant effect on work motivation, both partially and simultaneously. The dimension of "alignment with organizational values" was found to have the most dominant influence. The coefficient of determination (R2) value of 0.623 indicates that 62.3% of the variation in work motivation is influenced by workplace spirituality. The research implications suggest the need for a spiritual and religious values-based approach to enhance the meaning of work for employees.